Dana Desa, SDGs Desa dan Pembangunan Desa di Kabupaten Cianjur dan Bogor - Ramdani, Sandi Asep; Kharisma, Bayu; Hadiyanto, Ferry (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2024)
Cianjur and Bogor Regencies in West Java receive substantial Village Fund allocations but exhibit significant differences in IDM values. This study aims to analyze the contribution of village funds to Village SDGs achievement and their impact on IDM values in both regencies from 2018-2023, using mapping of village fund activity codes, panel data regression, and difference in differences (DiD). The results show that village fund activities in both regencies primarily support Village SDGs number 9 (Village Infrastructure and Innovation). However, in Cianjur, IDM is most influenced by activities in Village SDGs number 13, while in Bogor, SDGs number 16 has the greatest impact. DiD analysis reveals that implementing Village SDGs in Bogor is more effective than in Cianjur. These findings suggest that Village Government need to optimize IDM achievements through Village Fund activities depends on each village's characteristics, with a balanced focus beyond physical infrastructure being crucial for rural development.